Lead-zinc alloy powder and preparation method and application thereof

By coating lead powder on the surface of zinc powder and forming lead-zinc gradient alloy powder, and using its internal electrolytic cell mechanism for electrochemical precipitation reaction, the problems of low efficiency and high cost of thallium removal in acid waste liquid in the prior art are solved, and the problem of low efficiency and high cost of thallium removal in acid waste liquid is achieved. It has efficient and economical deep thallium removal effect.

CN119457061APending Publication Date: 2025-02-18HUNAN UNIV OF TECH +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411558441.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, when dealing with the removal of thallium in acidic waste liquid, there are problems such as large reagent consumption and inadequacy, and the single zinc powder has poor effect on removing thallium, and the amount is large, and the cost is high.

Method used

Lead-zinc alloy powder is used to uniformly coat lead-zinc alloy powder on the surface of the zinc powder and degreasing and permeation treatment at high temperature to form lead-zinc gradient alloy powder. The electrochemical precipitation reaction is carried out using its internal electrolytic cell mechanism to improve the thallium Removal efficiency.

Benefits of technology

Deep thallium removal is achieved, significantly improving the thallium removal rate, reducing reagent consumption, reducing costs, and simplifying the preparation process to adapt to large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457061A_ABST
    Figure CN119457061A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of resource recovery, and discloses lead-zinc alloy powder as well as a preparation method and application thereof. The content of lead in the lead-zinc alloy powder is gradually reduced from the surface to the center of the lead-zinc alloy powder. The lead-zinc combination in the lead-zinc alloy reaches the atomic level, an internal electrolytic tank with lead as a cathode and zinc as an anode is formed during thallium removal, and an ordered electrochemical precipitation reaction is provided instead of disordered random replacement, so that the thermodynamic driving force of thallium precipitation is improved, the thallium precipitation effect is enhanced, deep thallium removal is realized, and the thallium removal rate is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of resource recovery, relates to the recovery of thallium in acidic waste liquid, and specifically relates to a lead-zinc alloy powder and a preparation method and application thereof. Background Art

[0002] During the smelting process of lead, zinc and iron sulfides, a large amount of thallium-containing acidic waste liquid is easily generated. Thallium is a highly toxic element, which is more toxic than highly toxic heavy metals such as cadmium, mercury and lead, and has strong bioaccumulation, posing a great threat to the human body and the ecological environment. The thallium element in the waste liquid needs to be recovered before it is discharged.

[0003] At present, the most effective methods for removing thallium from acidic wastewater are precipitation, adsorption and replacement. The precipitation method can be divided into oxidation precipitation and sulfide precipitation, which are based on the principle of using Tl(OH) 3 and Tl 2 S has a very low solubility product. Adding an oxidant or sulfiding agent to the solution will cause thallium to precipitate and be removed. The adsorption method uses the porous and high specific surface characteristics of the adsorbent to adsorb thallium into the adsorbent, thereby removing thallium. The precipitation method and adsorption method are prone to cause problems such as large reagent consumption and inadaptability in the treatment of acidic solutions.

[0004] Using the positive potential characteristic of thallium, the zinc powder replacement method is also a commonly used method. This method is not easy to affect the solution, but the single zinc powder has a poor effect on thallium removal and a large amount of use. CN109957668A discloses a process for purifying a wet zinc smelting solution and removing thallium. 200~800g / L of lead acetate is added to a purification tank to remove thallium. However, due to the high price of lead acetate and the presence of a large amount of sulfate in the solution, additional loss of lead acetate will result, resulting in a waste of cost. CN114438341A discloses the use of a composite zinc powder in the removal of thallium from a zinc sulfate solution. Metallic zinc powder and additive powder (lead powder or tin powder) are used as raw materials to prepare a composite zinc powder slurry, and lead-zinc composite powder is used to remove thallium from a thallium-containing acidic solution. However, this method of removing thallium is only a physical process, and the effect of zinc, lead, and tin in removing thallium from a thallium-containing acidic solution is limited. Summary of the invention

[0005] In view of the defects and shortcomings of the prior art, in the first aspect, the present invention provides a lead-zinc alloy powder; in the second aspect, the present invention provides a method for preparing the lead-zinc alloy powder; in the third aspect, the present invention provides an application of the lead-zinc alloy powder.

[0006] In a first aspect, the present invention provides a lead-zinc alloy powder, wherein the lead content in the lead-zinc alloy powder gradually decreases from the surface to the center of the lead-zinc alloy powder.

[0007] Preferably, the mass ratio of zinc to lead in the lead-zinc alloy powder is 1:0.05-1.

[0008] In a second aspect, the present invention provides a method for preparing a lead-zinc alloy powder, comprising the following steps: Step 1, wetting the surface of zinc powder with a wetting agent, and then adding lead powder to the wetted zinc powder and mixing until the lead powder is coated on the surface of the zinc powder to obtain lead powder-coated zinc powder; Step 2, degreasing and infiltrating the lead powder-coated zinc powder at high temperature, and obtaining the lead-zinc alloy powder after cooling; Among them, degreasing is carried out in a vacuum atmosphere, the heat treatment temperature is 200~230℃, and the heat treatment time is 1~3h; melt infiltration is carried out in an inert atmosphere, the heat treatment temperature is 320~360℃, and the heat treatment time is 1~6h.

[0009] Preferably, the wetting agent is a silane coupling agent.

[0010] Preferably, the wetting agent is any one or more of vinyl silane, amino silane, epoxy silane, mercapto silane and methacryloxy silane.

[0011] More preferably, the wetting agent is vinyl silane.

[0012] Preferably, the amount of the wetting agent added is 2% to 30% of the mass of the zinc powder.

[0013] Preferably, the mass ratio of the zinc powder to the lead powder is 1:0.05-1.

[0014] Preferably, the particle size of the zinc powder is 20-200 mesh; the particle size of the lead powder is 200-600 mesh.

[0015] Preferably, in step 2, during degreasing, the vacuum degree is 5-100 Pa; during infiltration, the inert gas providing the inert atmosphere is any one or both of nitrogen and argon.

[0016] In a third aspect, the present invention provides an application of a lead-zinc alloy powder, wherein the lead-zinc alloy powder or the lead-zinc alloy powder prepared by the above preparation method is added to an acidic waste liquid containing thallium to remove thallium.

[0017] Preferably, the mass ratio of the lead-zinc alloy powder to the thallium in the thallium-containing acidic waste liquid is 8-120:1.

[0018] Preferably, the thallium removal temperature is 20-80° C., and the thallium removal time is 0.5-2 h.

[0019] Compared with the prior art, the present invention has at least one of the following beneficial effects: (1) When removing thallium, the lead-zinc alloy forms an internal electrolytic cell with lead as the cathode and zinc as the anode, providing an orderly electrochemical precipitation reaction rather than a disorderly random replacement, thereby increasing the thermodynamic driving force for thallium precipitation, strengthening the thallium precipitation effect, achieving deep thallium removal, and significantly improving the thallium removal rate.

[0020] (2) The preparation method provided by the present invention can simply prepare uniform lead-zinc gradient alloy powder material. The surface of the zinc powder is first wetted to make the ultrafine lead powder evenly adhere to the surface of the zinc powder, and the wetting agent is removed and the lead-zinc gradient alloying is performed in sequence through vacuum degreasing and high-temperature infiltration. The preparation process has strong standardization, which is conducive to the large-scale preparation of lead-zinc alloy powder with uniform organization and structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A flow chart of a method for preparing a lead-zinc alloy provided by the present invention; Figure 2 This is the XRD diagram of the lead-zinc alloy prepared in Example 1 of the present invention; Figure 3 This is a SEM image of a cross section of the lead-zinc alloy prepared in Example 1 of the present invention; Figure 4 This is a SEM-EDS image of zinc in the thallium-removed slag obtained after thallium is removed from the lead-zinc alloy prepared in Example 1 of the present invention; Figure 5 This is a SEM-EDS image of lead in the thallium-removed slag obtained after thallium is removed from the lead-zinc alloy prepared in Example 1 of the present invention; Figure 6 This is a SEM-EDS image of thallium in the thallium-removed slag obtained after thallium is removed from the lead-zinc alloy prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The present invention provides the following specific technical solutions.

[0023] In a first aspect, the present invention provides a lead-zinc alloy powder, wherein the lead content in the lead-zinc alloy powder gradually decreases from the surface to the center of the lead-zinc alloy powder.

[0024] In the prior art, zinc powder and additive powder (lead powder or tin powder) are usually directly added to the thallium-containing sulfuric acid waste liquid to carry out a simple replacement reaction, and the thallium removal effect is limited. After research, the inventor found that by optimizing the structure of the lead-zinc alloy, adding lead to the zinc powder for alloying, the lead and zinc are combined at the atomic level, and the lead-zinc alloy powder is replaced to remove thallium. The thallium removal reaction mainly occurs on the surface of the zinc powder. The free thallium ions in the solution diffuse into the surface and interior of the zinc powder and undergo a precipitation reaction. In the gradient alloy powder, an internal electrolytic cell with lead as the cathode and zinc as the anode is formed, and the precipitation of thallium is enhanced by electrochemistry. The thallium removal reaction mainly occurs on the surface of the zinc powder. The further into the particle, the weaker the reaction, so that the reaction intensity weakening route is consistent with the alloy component gradient reduction route, further increasing the thallium removal rate.

[0025] Preferably, the mass ratio of zinc to lead in the lead-zinc alloy powder is 1:0.05-1.

[0026] In a second aspect, the present invention provides a method for preparing a lead-zinc alloy powder, comprising the following steps: Step 1, wetting the surface of zinc powder with a wetting agent, and then adding lead powder to the wetted zinc powder and mixing until the lead powder is coated on the surface of the zinc powder to obtain lead powder-coated zinc powder; Step 2, degreasing and infiltrating the lead powder-coated zinc powder at high temperature, and obtaining the lead-zinc alloy powder after cooling; Among them, degreasing is carried out in a vacuum atmosphere, the heat treatment temperature is 200~230℃, and the heat treatment time is 1~3h; melt infiltration is carried out in an inert atmosphere, the heat treatment temperature is 320~360℃, and the heat treatment time is 1~6h.

[0027] By using a high-viscosity wetting agent to wet the surface of zinc powder, a uniform lead-zinc mixed powder is formed after adding lead powder. The lead powder can form a good wrap on the surface of the zinc powder particles, so that after heat treatment, an alloy powder with a uniform structure can be formed. The lead content in the alloy powder gradually decreases from the surface to the center of the lead-zinc alloy powder. The wetting agent is removed through two-stage heat treatment (degreasing and infiltration), and organic matter (wetting agent) is not brought into the melt without affecting the composition and structure of the alloy powder; and the lead is infiltrated into the zinc powder to form an alloy powder with a concentration gradient from the outside to the inside and atomic-level contact.

[0028] Degreasing in a vacuum atmosphere is conducive to the removal of organic matter (wetting agent), preventing the organic matter from forming a coating layer during the subsequent heat treatment process, which hinders the diffusion of lead during the infiltration process; it also avoids bringing organic matter into the solution to be treated (acidic waste liquid containing thallium) to prevent secondary contamination of the solution to be treated.

[0029] In actual operation, melt infiltration is carried out under normal pressure. The vacuum environment will intensify the volatilization of zinc and lead, resulting in waste of raw materials.

[0030] Preferably, the wetting agent is a silane coupling agent, and the amount of the wetting agent added is 2-30% of the mass of the zinc powder.

[0031] Preferably, the wetting agent is any one or more of vinyl silane, amino silane, epoxy silane, mercapto silane and methacryloxy silane.

[0032] More preferably, the wetting agent is vinyl silane.

[0033] Preferably, the amount of the wetting agent added is 2% to 30% of the mass of the zinc powder.

[0034] More preferably, the wetting agent is added in an amount of 5% to 10% of the mass of the zinc powder.

[0035] Preferably, the mass ratio of the zinc powder to the lead powder is 1:0.05-1.

[0036] Preferably, the particle size of the zinc powder is 20-200 mesh; the particle size of the lead powder is 200-600 mesh.

[0037] In practical applications, the particle size of lead powder is smaller than that of zinc powder, which is conducive to the lead powder being wrapped on the surface of zinc powder, and then conducive to the lead infiltration into the zinc powder to form a lead-zinc alloy.

[0038] Preferably, in step 2, during degreasing, the vacuum degree is 5-100 Pa; during infiltration, the inert gas providing the inert atmosphere is any one or both of nitrogen and argon.

[0039] In a third aspect, the present invention provides an application of a lead-zinc alloy powder, wherein the lead-zinc alloy powder or the lead-zinc alloy powder prepared by the above preparation method is added to an acidic waste liquid containing thallium to remove thallium.

[0040] Preferably, the mass ratio of the lead-zinc alloy powder to the thallium in the thallium-containing acidic waste liquid is 8-120:1.

[0041] Preferably, the reaction temperature is 20-80° C. and the reaction time is 0.5-2 h.

[0042] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0043] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0045] Embodiment 1: A method for preparing lead-zinc alloy powder comprises the following steps: Step 1, taking 1000 g of zinc powder with an average particle size of 120 meshes, adding 50 g of vinyl silane thereto, stirring evenly, so that the silane coupling agent wets the surface of the zinc powder; then taking 50 g of lead powder with an average particle size of 300 meshes, adding the lead powder to the wetted zinc powder, mixing evenly until the lead powder is evenly coated on the surface of the zinc powder, to obtain lead-coated zinc powder; Step 2, heat treating the lead-coated zinc powder; first degreasing, transferring the lead-coated zinc powder to an infiltration furnace, extracting the gas in the infiltration furnace until the vacuum degree in the infiltration furnace is 20Pa, and then heat treating the lead-coated zinc powder at 215°C for 2h in a vacuum atmosphere; then entering the infiltration stage, introducing nitrogen into the infiltration furnace until the air pressure in the infiltration furnace returns to normal pressure, and then heating to 330°C to heat treat the lead-coated zinc powder for 3h, cooling with the furnace, and obtaining a lead-zinc alloy.

[0046] The solid particles that have been defatted in step 2 were sampled and analyzed, and the residual fat rate was measured to be 0.58%, proving that most of the wetting agent was removed under vacuum and negative pressure conditions.

[0047] Figure 2 The XRD pattern of the lead-zinc alloy obtained in Example 1 is shown in FIG. Figure 2 It can be seen that the peaks of Zn and Pb appear in the XRD diffraction spectrum, among which the peak of zinc is the main phase and lead is the secondary phase, which is proportional to the amount of lead and zinc added.

[0048] Figure 3 The SEM image of the lead-zinc alloy cross section obtained in Example 1 is shown in FIG. Figure 3 It can be seen that there is a continuous melting and infiltration process of lead from lead to zinc matrix, with a large amount of lead concentrated on the surface and zinc mainly in the interior. Figure 3 Point 1, point 2 and point 3 are taken from the outside to the inside in the radial direction of the cross section of the lead-zinc alloy shown in the figure, and EDS analysis is performed on them. The contents of lead and zinc at the three points are shown in Table 1.

[0049] Table 1 Lead and zinc contents at points 1, 2 and 3 Location Point 1 Point 2 Point 3 Pb 76.26% 21.02% 2.15% Zn 22.19% 77.80% 97.66% As can be seen from Table 1, the lead contents on the surface, in the middle and inside are 76.26%, 21.02% and 2.15% respectively, which proves that the lead in the lead-zinc alloy prepared by the preparation method provided by the present invention is distributed in a gradient, and the lead content decreases from the outside to the inside.

[0050] Embodiment 2: A method for preparing lead-zinc alloy powder comprises the following steps: Step 1, taking 1000g of zinc powder with an average particle size of 20 meshes, adding 100g of aminosilane thereto, stirring evenly, so that the silane coupling agent wets the surface of the zinc powder; then taking 500g of lead powder with an average particle size of 200 meshes, adding the lead powder to the wetted zinc powder, mixing evenly until the lead powder is evenly coated on the surface of the zinc powder, to obtain lead-coated zinc powder; Step 2, heat treating the lead-coated zinc powder; first degreasing, transferring the lead-coated zinc powder to an infiltration furnace, extracting the gas in the infiltration furnace until the vacuum degree in the infiltration furnace is 5 Pa, and then heat treating the lead-coated zinc powder at 200° C. for 1 hour in a vacuum atmosphere; then entering the infiltration stage, introducing nitrogen into the infiltration furnace until the air pressure in the infiltration furnace returns to normal pressure, and then heating to 320° C. to heat treat the lead-coated zinc powder for 1 hour, cooling with the furnace, and obtaining a lead-zinc alloy.

[0051] The solid particles that have been defatted in step 2 were sampled and analyzed, and the residual fat rate was measured to be 0.32%, proving that most of the wetting agent was removed under vacuum and negative pressure conditions.

[0052] Embodiment 3: A method for preparing lead-zinc alloy powder comprises the following steps: Step 1, taking 1000 g of zinc powder with an average particle size of 200 meshes, adding 300 g of epoxy silane thereto, stirring evenly, so that the silane coupling agent wets the surface of the zinc powder; then taking 100 g of lead powder with an average particle size of 600 meshes, adding the lead powder to the wetted zinc powder, mixing evenly until the lead powder is evenly coated on the surface of the zinc powder, to obtain lead-coated zinc powder; Step 2, heat treating the lead-coated zinc powder; first degreasing, transferring the lead-coated zinc powder to an infiltration furnace, extracting the gas in the infiltration furnace until the vacuum degree in the infiltration furnace is 100 Pa, and then heat treating the lead-coated zinc powder at 230° C. for 3 hours in a vacuum atmosphere; then entering the infiltration stage, introducing nitrogen into the infiltration furnace until the air pressure in the infiltration furnace returns to normal pressure, and then heating to 360° C. to heat treat the lead-coated zinc powder for 1 hour, cooling with the furnace, and obtaining a lead-zinc alloy.

[0053] The solid particles that have been defatted in step 2 were sampled and analyzed, and the residual fat rate was measured to be 0.75%, proving that most of the wetting agent was removed under vacuum and negative pressure conditions.

[0054] Comparative Example 1: A thallium removing agent comprises: 1000g zinc powder and 50g lead powder, wherein the average particle size of the zinc powder is 120 meshes, and the average particle size of the lead powder is 300 meshes. The thallium removing agent is obtained by uniformly mixing the zinc powder and the lead powder.

[0055] The lead-zinc alloy prepared in Example 1 and the thallium removal agent obtained in Comparative Example 1 were used for thallium removal test. 1.0 g of the lead-zinc alloy prepared in Examples 1 to 3 and the thallium removal agent prepared in Comparative Example 1 were added to 1000 mL of thallium-containing acidic melt, respectively, and reacted at a temperature of 40° C. for 2 h to perform thallium removal reaction. After the reaction, the thallium removal liquid was filtered, and the solid particles obtained by filtration were the thallium removal slag. The test results are shown in Table 2.

[0056] Table 2 Thallium removal rates of the lead-zinc alloy obtained in Example 1 and the thallium removal agent obtained in Comparative Example 1 It can be seen from Table 2 that the lead-zinc alloy provided by the present invention can greatly improve the efficiency of thallium removal.

[0057] The thallium-removed slag obtained after thallium removal from the lead-zinc alloy prepared in Example 1 was subjected to SEM-EDS analysis. Figure 4 This is the SEM-EDS image of zinc in thallium removal slag. Figure 5 This is the SEM-EDS image of lead in thallium slag. Figure 6 is the SEM-EDS image of thallium in the thallium removal slag; Figure 5 and Figure 6 It can be seen that the distribution of thallium is also high in the lead-rich area, and the two form a consistent distribution behavior, which confirms the principle of the internal battery with lead as the cathode, that is, the precipitated thallium is deposited on the lead cathode.

[0058] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A lead-zinc alloy powder, characterized in that: The content of lead in the lead-zinc alloy powder gradually decreases from the surface to the center of the lead-zinc alloy powder.

2. The lead-zinc alloy powder according to claim 1, characterized in that The mass ratio of zinc to lead in the lead-zinc alloy powder is 1:0.05-1.

3. A method for preparing lead-zinc alloy powder, characterized in that: The steps include: Step 1, wetting the surface of zinc powder with a wetting agent, and then adding lead powder to the wetted zinc powder and mixing until the lead powder is coated on the surface of the zinc powder to obtain lead powder-coated zinc powder; Step 2, degreasing and infiltrating the lead powder-coated zinc powder at high temperature, and obtaining the lead-zinc alloy powder after cooling; Among them, degreasing is carried out in a vacuum atmosphere, the heat treatment temperature is 200~230℃, and the heat treatment time is 1~3h; melt infiltration is carried out in an inert atmosphere, the heat treatment temperature is 320~360℃, and the heat treatment time is 1~6h.

4. The method for preparing a lead-zinc alloy according to claim 3, characterized in that: The mass ratio of the zinc powder to the lead powder is 1:0.05-1; the particle size of the zinc powder is 20-200 meshes; and the particle size of the lead powder is 200-600 meshes.

5. The method for preparing the lead-zinc alloy according to claim 3, characterized in that: The wetting agent is a silane coupling agent.

6. The method for preparing a lead-zinc alloy according to claim 5, characterized in that: The wetting agent is any one or more of vinyl silane, amino silane, epoxy silane, mercapto silane and methacryloxy silane.

7. The method for preparing a lead-zinc alloy according to claim 3, characterized in that: The amount of the wetting agent added is 2% to 30% of the mass of the zinc powder.

8. The method for preparing a lead-zinc alloy according to claim 3, characterized in that: In step 2, during degreasing, the vacuum degree is 5-100 Pa; during infiltration, the inert gas providing the inert atmosphere is any one or both of nitrogen and argon.

9. An application of lead-zinc alloy powder, characterized in that: The lead-zinc alloy powder described in any one of claims 1 to 2 or the lead-zinc alloy powder prepared by the preparation method described in any one of claims 3 to 8 is added to the acidic waste liquid containing thallium to remove thallium.

10. The use of the lead-zinc alloy powder according to claim 9, characterized in that: The mass ratio of the lead-zinc alloy powder to the thallium in the thallium-containing acidic waste liquid is 8-120:1.

Citation Information

Patent Citations

  • Technology method for purifying zinc hydrometallurgy solution and removing thallium

    CN109957668A

  • Application of compound zinc powder in thallium removal of zinc sulfate solution

    CN114438341A

  • Method for preparing aerated concrete by utilizing lead zinc tailings

    CN103342510A

  • Metal-coated powder surface alloying method

    CN103691938A

  • Gradient alloying powder material prepared by high-temperature thermal diffusion method and preparation method therefor

    CN113145843A